Documentation Bulletin No. 7. - Planning Commission (Planning Commission, 1970)
The P.E.O. at the instance of the Planning Commission carried cut detailed evaluation studies of High Yielding Varieties Programme during 1967-68. The Ministry of Food & Agriculture, While initiating prompt follow-up action on these reports, desired the study to be conducted for the agricultural year 1968-69 also. The field work was carried out during Kharif, 1958 covering 974 participant and 643 non-participant cultivators spread over 44 development blocks for paddy, bajra, jowar and maize.
Programme Evaluation Organisation Planning Commission Government of India